The Effect Of Sweet Below Consumption On Hemoglobine Levels In Pregnant Women At Bpm Hj. Eniyati Kecamatan Banjar Pandeglang District In 2020 - Erisa Auliantika; Triana Indrayani; Cholisah Suralaga (UrbanGreen, 2020)
Anemia in pregnancy can have devastating effects on both the mother and the fetus. The prevalence of anemia cases in pregnant women nationwide in 2018 was 48.9%. Anemia cases of pregnant women at Banjar Puskesmas in 2019 amounted to 62.22% and cases of anemia for pregnant women at BPM Hj. Eniyati in 2020 amounted to 67.81%. The average value of hemoglobin levels of pregnant women in the control group before treatment (pretest) was 9.85 gr / dl and after treatment (posttest) was 10.52 gr / dl. Whereas in the intervention group the average value of hemoglobin levels for pregnant women before treatment (pretest) was 9.74 gr / dl and after treatment (posttest) was 11.15 gr / dl. The statistical test results obtained p value = 0.000. There is an effect of consumption of sweet starfruit juice on hemoglobin levels in pregnant women at BPM Hj. Eniyati, Banjar District, Pandeglang Regency in 2020. It is recommended for pregnant women to check their Hb levels regularly and regularly consume Fe tablets of at least 90 tablets during pregnancy accompanied by consuming fruits containing vitamin C, one of which is sweet star fruit, which can increase hemoglobin levels.